2008
DOI: 10.1080/02844310802098458
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitivity in a reconstructed microtic ear

Abstract: The aim of this study was to evaluate thermo-thresholds in autologous reconstructed microtic ears. Nineteen patients with unilateral microtia were investigated no less than two years after the last operation (3.6+/-1.7 years). Their normal corresponding ear acted as controls. Eight healthy children were also investigated to illustrate technical differences between measuring the two sides. Thermal sensitivity was tested quantitatively using a SENSELab MSA Thermotest. The skin temperature was also tested. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Temperature was significantly higher in the reconstructed ear in the upper Blood flow dynamics in reconstructed auricles 315 region. This is in agreement with our previous study on thermosensibility, where actually all three regions showed increased temperatures [4]. A tentative explanation to this difference is that the normal ear is a little more slender and protruding compared with the reconstructed ear facilitating heat convection to the ambient air.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Temperature was significantly higher in the reconstructed ear in the upper Blood flow dynamics in reconstructed auricles 315 region. This is in agreement with our previous study on thermosensibility, where actually all three regions showed increased temperatures [4]. A tentative explanation to this difference is that the normal ear is a little more slender and protruding compared with the reconstructed ear facilitating heat convection to the ambient air.…”
Section: Discussionsupporting
confidence: 92%
“…Nerves and vessels are necessarily bisected when incising and undermining the area. Despite this fact both thermo-sensitivity and tactile sensitivity recover to acceptable levels [4,5]. The nervous mechanisms regulating the blood supply could be restituted in analogy.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few reports about the skin sensitivity of a normal ear [12,13], and a MEDLINE search (key words: skin sensitivity, reconstructed auricle) gave no results about the reconstructed auricle, except for our own previous report on its thermosensitivity [14].…”
Section: Many Reports Have Been Published About the Different Surgicamentioning
confidence: 83%
“…The ears had been reconstructed from 1995-2008. The median age of the patients at the time of reconstruction was 10.5 years (range 6-19); median age 13 years (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) at the time of follow-up, and median time after the reconstruction 20 months (6-60).…”
Section: Patientsmentioning
confidence: 99%
“…porous polyethylene or autologous rib cartilage, respectively [2]. Benefits with an ear made of autologous rib cartilage are that it is sensitive for touch and temperature, and has a very good colour match [3,4]. The main disadvantage with porous polyethylene implant is the risk of extrusion, which does not exist for autologous rib cartilage.…”
Section: Introductionmentioning
confidence: 99%